2021
DOI: 10.2478/johh-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Relative role of sediment entrainments on log-law parameters of longitudinal velocity distributions in mobile bed flows

Abstract: In alluvial channel, the non-cohesive bed particles are frequently accelerated by the flows and there has been an inconclusive debate on the deviations of logarithmic law parameters that demonstrate the velocity distributions in flows. Present study aims to elucidate the current knowledge of overwhelming theoretical and experimental evidences in this regard within the scope of near-bed turbulent flow characteristics. The study was conducted in two folds collecting instantaneous velocity of flow over a rigid sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…where κ is the von Kármán coefficient which remains constant (κ ≈ 0.4) over semi-rigid boundary e.g., an armored river bed in a gravel bed river, and u f1 and u f2 are local flow velocity values at 20% and 80% of the flow depth from the water surface in a velocity profile, respectively, along with vertical distances y 1 and y 2 of these points from the water surface. However, it is important to note that this method is not recommended for sandbed rivers when sediment entrainment occurs, as the log law exhibits a decrease in the von Kármán constant (Dey, 2014;Malakar and Das, 2021). Numerous studies have demonstrated that flow resistance is enhanced by sediment-laden flow, resulting in reduced flow velocity and an increase in the ratio of bed-roughness scale to the moving sediment layer (Ferro, 2018b;Mendicino and Colosimo, 2019).…”
Section: Methodology Frameworkmentioning
confidence: 99%
“…where κ is the von Kármán coefficient which remains constant (κ ≈ 0.4) over semi-rigid boundary e.g., an armored river bed in a gravel bed river, and u f1 and u f2 are local flow velocity values at 20% and 80% of the flow depth from the water surface in a velocity profile, respectively, along with vertical distances y 1 and y 2 of these points from the water surface. However, it is important to note that this method is not recommended for sandbed rivers when sediment entrainment occurs, as the log law exhibits a decrease in the von Kármán constant (Dey, 2014;Malakar and Das, 2021). Numerous studies have demonstrated that flow resistance is enhanced by sediment-laden flow, resulting in reduced flow velocity and an increase in the ratio of bed-roughness scale to the moving sediment layer (Ferro, 2018b;Mendicino and Colosimo, 2019).…”
Section: Methodology Frameworkmentioning
confidence: 99%
“…An unpleasant complication is the fact that the occurrence and amount of sediments can change in time and space depending on the occurrence of water flow rates in the sewer (e.g. during rainstorms) (Dodangeh and Afzalimehr, 2022;Malakar and Das, 2021) Adding our experience from this study (see Figure 2) to our previous research results (Sokáč et al, 2019), we can state, that practically all dispersion solution methods, based on the "classical" ADE and the Gaussian analytical solution have proven to be very inaccurate in real conditions. This finding was very disturbing especially since the basic principle of the localisation procedure is precisely the match rate between the modelled and simulated pollutograms.…”
Section: Monitoring Point Event Registrationmentioning
confidence: 99%